PENINGKATAN KREATIVITAS MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING DI KELAS IV MIN KOTA JAYAPURA - Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2022)
This study aims to increase science creativity through cooperative learning in grade 4 MIN Jayapura City. This type of research is a class action research of 2 cycles. Each cycle consists of 4 stages: planning, implementation of the action, observation and reflection. The research subjects were students of grade 4 MIN Jayapura City. Data collection techniques using observation. There is an increase in student creativity, as indicated by student attitudes when participating in learning in each cycle. In cycle I, with a percentage of 74%, including sufficient criteria. In cycle II, a percentage of 92.5% was obtained with very good creativity criteria. The cooperative learning model can increase science creativity in grade 4 MIN Jayapura City.